Effects of attentional and cognitive variables on unilateral spatial neglect. (November 2016) - Ricci, Raffaella; Salatino, Adriana; Garbarini, Francesca; Ronga, Irene; Genero, Rosanna; Berti, Anna; Neppi-Mòdona, Marco
Abstract: Patients with visuospatial neglect when asked to cancel targets partially or totally omit to cancel contralesional stimuli. It has been shown that increasing the attentional demands of the cancellation task aggravates neglect contralesionally. However, some preliminary evidence also suggests that neglect might be worsened by engaging the patient in a demanding, non-spatial, cognitive activity (i.e. a mathematical task). We studied cancellation performance of 16 patients with right-hemisphere lesions, 8 with neglect, 8 without neglect, and 8 age-matched healthy control participants by means of five cancellation tasks which varied for the degree of attentional and/or high level cognitive demands (preattentive and attentive search of a visual target, searching for numbers containing the digit 3, even numbers, and multiples of 3). Results showed that attentive search of visual targets, relative to the preattentive search condition, aggravated neglect patients' performance. Moreover, searching for multiples not only worsened spatial neglect contralesionally, but also slowed down performance of patients with right-hemisphere lesions without neglect. Our findings further demonstrate the presence of specific deficits of attention in neglect. In addition, the worse performance of patients without neglect in the 'multiples of 3' task is consistent with the evidence that right-hemisphere lesions per se impair the ability to maintain attention (i.e. sustained attention). This suggests that the exacerbation of neglect during execution of a demanding, non-spatial, cognitive task might be explained by a deficit of sustained attention in addition to a selective deficit of spatial attention. Highlights: Non spatial cognitive load worsens the spatial exploration bias in neglect. Spatial neglect is modulated by task-related sustained attention. Right hemisphere damage impairs sustained attention. Spatial neglect is modulated by cognitive other than perceptual task-related factors. Bottom up perceptual features and top down cognitive factors modulate spatial neglect.